2019
DOI: 10.1111/fwb.13359
|View full text |Cite|
|
Sign up to set email alerts
|

A three‐dimensional numerical model investigation of the impact of submerged macrophytes on flow dynamics in a large fluvial lake

Abstract: Aquatic plants (macrophytes) are known to affect flow dynamics, contributing to flow resistance. Most studies on flow‐vegetation interactions are performed in laboratory flumes and focus on the flow field around plants, with little research at the level of vegetation patches in large aquatic ecosystems. In most hydrodynamic models, increased drag due to plants is modelled by increasing the Manning's n roughness coefficient. The objectives of this study were to: (1) develop a three‐dimensional hydrodynamic mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 71 publications
2
7
0
Order By: Relevance
“…This is highlighted by the similar denitrification rates measured in a dense floating bed of Trapa natans in a sheltered bay of the Hudson River (1.5 km 2 , 518–994 mg N m −2 d −1 ), in contrast to the undetectable rates in a small (0.6 km 2 ) Vallisneria meadow in a fast‐flowing channel from the same river (Tall et al., 2011). The floating meadow acted in a similar way to this study large SAV meadow (∼10 km 2 ) that both intercepted nutrient‐rich waters and reduced velocities (Bulat et al., 2019), thus promoting high nitrate removal. Another line of evidence supporting the robustness of our estimates is that our measured uptake velocities ( V f , median 3.0 m d −1 ) were similar to those reported for the Upper Snake River (WY, USA, 12 m 3 s −1 , 0.6–13.0 m d −1 , Tank et al., 2008).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This is highlighted by the similar denitrification rates measured in a dense floating bed of Trapa natans in a sheltered bay of the Hudson River (1.5 km 2 , 518–994 mg N m −2 d −1 ), in contrast to the undetectable rates in a small (0.6 km 2 ) Vallisneria meadow in a fast‐flowing channel from the same river (Tall et al., 2011). The floating meadow acted in a similar way to this study large SAV meadow (∼10 km 2 ) that both intercepted nutrient‐rich waters and reduced velocities (Bulat et al., 2019), thus promoting high nitrate removal. Another line of evidence supporting the robustness of our estimates is that our measured uptake velocities ( V f , median 3.0 m d −1 ) were similar to those reported for the Upper Snake River (WY, USA, 12 m 3 s −1 , 0.6–13.0 m d −1 , Tank et al., 2008).…”
Section: Discussionsupporting
confidence: 60%
“…The cross‐sectional area was estimated from the sum of cell depths measured for the outflow transect on a bathymetric raster map (Hudon & Carignan, 2008), corrected for daily water level height, and multiplied by the bathymetric cell width. Daily velocity was estimated from Delft3D simulations, a tridimensional hydrodynamic model established for our study area (Bulat et al., 2019). Model simulations were run for each year using median, minimum, and maximum input discharges at Saint‐François over the SUNA mooring period and yearly spatial polygons of SAV height established from SAV echosounding surveys (Botrel et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…In this context, the hydraulic conveyance of vegetated open channels intersecting anthropogenic settlements is dramatically affected by the temporal evolution of riverine vegetation properties [9][10][11], mainly associated with riverine plants' growth, foliage, and density overall [12,13]. In fact, in the case of vegetated flows, the morphometric and bio-physical changes over time in riverine vegetation canopy features represent a source of hydraulic roughness, in addition to that due to the only riverbanks and bed, to be meticulously considered in the field-scale analysis of global flow resistance [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…For surface free wetland, vertical flow stratification and mixing due to bathymetry, inflows, weather conditions and vegetation are often neglected, while they can have considerable consequences: Sweeney et al (2003)'s three dimen-sional simulations showed that wind could change the residence time distribution from quasi plug flow into quasi fully mixed flow in a large waste stabilization pond, with high effects on the treatment efficiency; Adamsson et al (2005) attributed the unexpectedly high residence time of a tracer at low flow in a laboratory tank to the deep storage of the cool inflow. Bulat et al (2019) applied a three-dimensional model for the flow within rigid emergent and submerged vegetation to a large fluvial lake and showed the improvement of stratified flow description compared to the usual representation with a Manning-Strickler bottom roughness. Holland et al (2004) found experimentally that the flow rate had little impact on the hydraulic performance of a nonvegetated constructed wetland.…”
Section: Introductionmentioning
confidence: 99%